Room vs. Body Temperature to Evaluate Electrical Interface Parameters of State‐Of‐The‐Art PEDOT : PSS‐Based Electrodes - PhD. Eng. Karolina Cysewska (ChemElectroChem)
Abstract In this work, the effect of the simulated body fluid temperature on the electrical interface parameters of the state‐of‐the‐art PEDOT‐PSS electrode was studied. PEDOT‐PSS was synthesized by electrodeposition on graphite and gold‐coated‐graphite electrodes. All electrochemical measurements were performed in phosphate‐buffered saline aqueous solution (pH 7.4) at room temperature (25 °C) and body temperature (37 °C). The results of the work confirmed that the modification of the carbon or metallic electrode with conducting polymer PEDOT : PSS significantly reduced the interfacial impedance and improved charge storage capacity and current injection limit due to its high electroactive surface area, roughness and porosity compared to the bare substrates. The work showed that solution temperature is a critical factor that can influence the electrical interface parameters of electrodes for neural stimulation. Understanding and controlling these temperature‐dependent effects are essential for ensuring the reliability, safety, and efficacy of neural stimulation applications in both research and clinical settings.